Ehlers-Danlos syndrome type II in three siblings of a Saudi family. - Samdani, A.J. (European Journal of Pediatric Dermatology, 2003)
Ehlers-Danlos syndrome is a rare hereditary disorder of the connective tissue characterized by cutaneous fragility, hyperextensibility of skin and joint hypermobility. This report describes a Saudi family with father and his three siblings, personally observed, suffering from Ehlers-Danlos syndrome type II. All the three siblings had moderate skin laxity, mild bruising, abnormal healing and joint hyperextensibility, while the father displayed extremely flexible metacarpo-phalangeal and inter-phalangeal joints. The clinical signs and family history were suggestive of Ehlers-Danlos syndrome type II. Although there is no specific treatment for the latter, it is important to early recognize the disorder to properly manage these patients.